Seeding density in wheat: the more, the merrier? (Scientia Agricola, 2013)
Adjustment of seeding schemes is one of the crop management techniques that most influences grain yield components. This work aimed to characterize the potential grain yield and its components in wheat (Triticum aestivum L.) genotypes with contrasting tillering ability under different seeding densities and environments. Five experiments were conducted in split-plot design, each with ten cultivars (main plot), sown in five distinct seeding densities (subplots). Experiments were sown in three locations in southern Brazil in the years 2005, 2006 and 2007. The grain yield per plot and its yield components: number of fertile tillers, weight of 1,000 grains, ear weight and number of grains per ear were evaluated. Genotypes with reduced tillering ability expressed an increase in grain yield with an increase in seeding densities, however showing a reduction in ear weight. The number of grains per ear did not affect grain yield but was highly influenced by seeding densities. The compensatory effect was expressed by the weight of a thousand grains as a function of the experimental conditions in which the genotypes were evaluated, regardless of seeding densities used. Results pointed to differences among cultivars tested in specific locations and years.